From Identity to Evaluation: Political Reorientation among Generation Z Voters in Post-Conflict Aceh - Faisal, Naidi; Abdullah, Taufik; Mulyadi, Mulyadi; Abubakar, Muhammad bin; Muzaffarsyah, T. (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2025)
This article examines the political reorientation of Generation Z voters in Aceh, Indonesia, between the 2019 and 2024 presidential elections. In Aceh—a post-conflict region where Islamic values and inherited political affiliations continue to shape civic life—young voters have traditionally aligned with electoral choices informed by family ties, clerical influence, and communal expectations. Using a sequential explanatory research design, this study combines survey data from two election cycles (n=73 in 2019; n=267 in 2024) with 30 in-depth interviews across three public universities. Findings reveal a notable shift from identity-based loyalty toward a more evaluative form of political reasoning. By 2024, many respondents reported prioritizing leadership credibility, programmatic vision, and policy clarity over ethnic and religious affiliation. This transformation was catalyzed by increased exposure to diverse information via social media, peer deliberation, and civic engagement in academic settings. However, the shift unfolded amid significant tension, particularly from family members and educators who framed political choice as a moral imperative. Respondents navigated these pressures through selective compliance, quiet dissent, and emerging political autonomy. This behavioral shift is understood here as a form of selective identity politics, in which inherited affiliations remain relevant but are increasingly subjected to rational and ethical scrutiny. The study contributes to broader discussions on youth political agency, identity negotiation, and democratic participation in culturally embedded and post-conflict contexts.